Programmable OTA-Based Multifunction Active Filter - Abdulrahman Khalaf Al-Ali; Muhammad Taher Abuelma'atti; Rizwan Ali Tiwana (Active and Passive Electronic Components)
A fully programmable multifunction filter is presented. The filter uses four operational transconductance amplifiers and two capacitors. Analog switches are used to control the filter transfer function through a microcontroller. The user is provided control over the cutoff (or centre) frequency of the filter by controlling the auxiliary bias currents of the operational transconductance amplifiers via digital-to-analog converters. The circuit can simultaneously provide three programmable transfer functions in a single structure and can realize all the standard second-order filters. The circuit is attractive for VLSI implementation.